Assessing Destination Competitiveness of Mati City: Utilizing Importance-Performance Analysis - Lagman, Liwliwa; Bustillo, Ronald Joseph; Cubillas, Angelica; Danieles, Shane Anjela (La Ricerca, 2023)
This paper aims to assess the destination competitiveness of Mati City utilizing importance-performance analysis. This paper utilized a quantitative, non-experimental design using the correlation technique to recognize the different scales in the importance analysis of Mati City as a destination when examining 516 beach goers. The study used descriptive statistics, frequency, mean, Pearson r, and ANOVA for the statistical tools. The study reveals the competitive importance of Mati City as a Tourist Destination concerning services, safety and security, attraction, Festival, transportation, and cuisine are found to be very important. Thus, developing a competitiveness model for destinations could assist tourism stakeholders in the public and private sectors in identifying the location's strengths and weaknesses from the viewpoint of travelers, as well as in highlighting chances for tourism development and formulating plans to address any risks to future tourism. The competitive performance of Mati City as a Tourist Destination was outstanding in terms of services, safety and security, attraction, festivals, transportation, and cuisine. Therefore, development results should be given more weight in tourist performance evaluations. The results show that Mati City has an outstanding destination performance overall. This does not, however, imply that Mati City does not require renovation. Several sectors need upgrading to boost Mati City's standing as a travel destination. The results show that transportation rates are the best, indicating that Mati City has a solid infrastructure that increases efficiency and supports the tourism industry. Lastly, there is no significant difference in sex, age, and marital status, while educational attainment significantly differs in assessing the destination competitiveness of Mati City utilizing performance analysis.